THE STUDY OF SEPTIC TANK EMPTYING STRATEGY IN URBAN AREAS CASE STUDY OF PADANG CITY, WEST SUMATRA - Andrizal, Nadya Khairannisa; Aziz, Rizki; Sri Komala, Puti (Lingkar: Journal of Environmental Engineering, 2025)
Septic tank emptying in Padang City has not been effectively implemented. Low public participation and illegal disposal of fecal sludge into drainage systems and water bodies remains common. This study aims to assess how the households manage septic tank emptying and offers strategic recommendations using a SWOT analysis. The data obtained from questionnaires given to 100 households across all sub-districts, as well as interviews with stakeholders from the Dinas LH of Padang City about current desludging programs. The emptying practices were grouped into safe and unsafe emptying. Results show that only 26,33% of households manage septic tanks properly in terms of construction, emptying, and knowledge. Based on the SWOT analysis result, the household fecal sludge management in Padang City's is situated in the quadrant II, meaning existing opportunities can be used to deal with internal weaknesses. Recommended strategies include regulatory development, capacity building, community engagement, and regular monitoring and evaluation to support the implementation of safe emptying practices.